Investigation of prevalence of Babesia equi and Babesia caballi in horses turkey - Erdogmus, S. Zerrin; Balkaya, Ibrahim (Indian Veterinary Journal, 2006)
The aim of this study was to determine the prevalence of Babesia equi and Babesia caballi by serologic (IFAT and CFT) and microscopic examination in Marmara and Aegean regions. For this purpose, sera and microscopic slides were prepared and examined from 205 horses randomly chosen from 10 different cities in these regions in year 2003. Blood smears stained with Giemsa were examined for Babesia species, and found to be negative except for a horse from Izmir. In the serological tests :performed, IFAT was more sensitive and specific compared to CFT.